OLD WORLD PORCUPINE (RODENTIA, HYSTRICIDAE) REMAINS FROM THE LATE MESSINIAN OF PIEDMONT, NW ITALY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2015)
The goal of this paper is to describe a single upper molar and a fragmented radius of Old World porcupines recently discovered in the latest Messinian localities of Moncucco Torinese and Verduno in the Tertiary Piedmont Basin, NW Italy. The available material can be assigned to the large-sized species Hystrix (Hystrix) depereti, rarely found in the late Turolian and early Ruscinian of Europe. A combined comparative and morphofunctional analysis of the fragmented radius suggest that Hystrix (Hystrix) depereti was characterized by a generalized terrestrial locomotory behaviour thus being very similar to extant Old World porcupines. Paleobiogeography and paleoecological consequences are also discussed.
Keywords: Rodentia; Hystricidae; locomotory behaviour; Messinian; Tertiary Piedmont Basin; Italy